Cara Telkomsel Melakukan dan Menerapkan Riset Informasi Pemasaran - Naifa, Naifa Aulia Husna; Hendra Riofita (PENG: Jurnal Ekonomi dan Manajemen, 2025)
ABSTRACT This research aims to analyze the application of marketing information research at Telkomsel, with a focus on the methods used and their impact on the marketing strategies implemented. The methods applied include digital surveys via the tSurvey.id platform and indirect interviews in the Customer Relationship Management (CRM) study. The results of the research show that Telkomsel can better identify market trends and optimize customer experience through an improved CRM system, which ultimately contributes to increased customer loyalty. The implications of this research emphasize the importance of ongoing marketing research for Telkomsel to remain competitive in the increasingly dynamic telecommunications industry and to increase overall customer satisfaction.   Keywords: Marketing Research; Telkomse